2010
DOI: 10.1007/s11999-010-1413-6
|View full text |Cite
|
Sign up to set email alerts
|

The Current Practice of Orthopaedic Oncology in North America

Abstract: This information can assist the fellowship directors and related professional societies in tailoring their educational programs and the interested orthopaedic resident to make a more informed career choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 15 publications
3
20
1
5
Order By: Relevance
“…In our experience, much of the emphasis in the orthopaedic oncology workforce and educational issues is focused on sarcoma treatment [1,15]. The results of this study emphasize that there is a significant need for the skills of an orthopaedic oncologist outside of sarcoma treatment and this must factor into these discussions.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…In our experience, much of the emphasis in the orthopaedic oncology workforce and educational issues is focused on sarcoma treatment [1,15]. The results of this study emphasize that there is a significant need for the skills of an orthopaedic oncologist outside of sarcoma treatment and this must factor into these discussions.…”
Section: Discussionmentioning
confidence: 87%
“…For example, many limb salvage procedures are lengthier than arthroscopies or even most arthroplastys, which may skew the numbers. However, a direct comparison to established orthopaedic oncologists showed that early-career surgeons performed a median of 23 annual procedure on sarcomas, which is less than half of the 58 average annual sarcomas reported by the MSTS membership [15]. There are a number of possible explanations for the relatively low productivity in the group we surveyed.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations